Desegregating the dollar : African American consumerism in the twentieth century - Weems, Robert E., 1951- (New York : New York University Press, 1998)
Despite African Americans' nearly $500 billion collective annual spending power, surprisingly little attention has been devoted to the ways U.S. businesses have courted black dollars in postslavery America. Desegregating the Dollar presents the first fully integrated history of black consumerism during the last century.
The World War I-era "Great Migration" of African Americans from the rural South to northern and southern cities stimulated initial corporate interest in blacks as consumers. A generation later, as black urbanization intensified during World War II and its aftermath, the notion of a distinct, profitable African American consumer market gained greater currency. Moreover, black socioeconomic gains resulting from the Civil Rights Movement, which itself featured such consumer justice protests as the Montgomery Bus Boycott, further enhanced the status and influence of African American shoppers
Unwilling to settle for facile black-and-white answers, Weems also explores the roles of blacks who promoted the importance of the African American consumer market to U.S. corporations. Their actions, ironically, set the stage for the ongoing destruction of black-owned businesses. While the extent of educational, employment, and residential desegregation remains debatable, African American consumer dollars have, by any standard, been fully incorporated into the U.S. economy. Basing his conclusions on exhaustive research in trade journals and other primary and secondary materials, Robert E. Weems Jr. has given us the definitive account of the complicated relationship between African Americans, capitalism, and consumerism.
The birth and development of the African American consumer market, 1900-1940 -- New world a-coming: Black consumers, 1941-1960 -- African American consumer activism before and during the Civil Rights era -- The revolution will be marketed: American corporations and Black consumers during the 1960s -- Blaxploitation and big business: American corporations and Black consumers during the 1970s -- A tale of two markets: African American consumers during the 1980s -- Epilogue: the changing same: American corporations and Black consumers during the 1990s -- Appendix: national negro business league Black consumer questionnaire, 1931.
Includes bibliographical references and index.
English.
Print version record.
JSTOR
Keywords: African American consumers -- History -- 20th century; Racism -- United States -- History -- 20th century; Consommateurs noirs américains -- Histoire -- 20e siècle.; Racisme -- États-Unis -- Histoire -- 20e siècle.; BUSINESS & ECONOMICS -- Consumer Behavior; BUSINESS & ECONOMICS -- Commercial Policy; African American consumers; Racism; United States; Verbrauch; USA; Schwärze; Consumentisme; Rassendiscriminatie; 1900-1999; History